Novel manufacturing approaches to solid-state batteries - Dörrer, C (2022)
All-solid-state batteries (SSBs) based on sulfide solid electrolytes (SEs) have the potential to increase safety and provide greater energy density compared to lithium-ion batteries (LIBs). To match the high capacity of metallic anodes, SSBs require high energy density, long-lasting composite cathodes such as those based on lithium Ni-Mn-Co (NMC) oxide mixed with a solid-state electrolyte (SE). However in practice, cathode capacity typically fades due to NMC cracking and increasing NMC/SE interface debonding because of NMC pulverization. Using smart processing protocols, a single-crystal particulate LiNi0.83Mn0.06Co0.11O2 and Li6PS5Cl SE composite cathode was fabricated with outstanding discharge capacity of 210 mA h g−1 and high areal capacity of 8.7 mA h cm−2 at 30 °C. A first cycle coulombic efficiency of >85%, and >99% thereafter, was achieved despite a 5.5% volume change during cycling.